INCREASING COMMUNITY PARTICIPATION THROUGH THE NEIGHBOURHOOD WATCH PROGRAMME TO PREVENT THEFT IN TANJUNG GUSTA SUB-DISTRICT, MEDAN HELVETIA DISTRICT: AN ACTION RESEARCH STUDY - Winda Kustiawan Winda Kustiawan; Iskandar Mandika Sebayang; Aldino Firmansyah (Jurnal Ikhtibar Nusantara, 2026)
Theft in urban areas is often triggered by weak neighborhood supervision and weak social cohesion among residents. This action research aims to increase community participation in Tanjung Gusta Village, Medan Helvetia District, by optimizing the Neighborhood Security System (Siskamling) program to prevent theft. Using qualitative methods with an action research approach, data was collected through participant observation, documentation, and in-depth interviews focused specifically on the Neighborhood Head as the local authority and the local community as the community's mass base. The results of the study indicate that before the action intervention, community participation was at a very low level due to the high level of individualism in urban communities and boredom with the old patrol management. Through the action research stages (planning, action, observation, and reflection), the researcher, together with the Neighborhood Head and residents, succeeded in reconstructing a transparent night patrol schedule, renovating the physical facilities of the post, and integrating the neighborhood reporting system. This intervention not only significantly increased the presence of residents in patrols to 90%, but also succeeded in re-establishing informal social control which was effective in reducing the crime rate of theft to zero cases in the area.